Aktivitas Fisik Mahasaiswa Program Studi Pendidikan Jasmani UN PGRI Kediri Pada Masa Pandemi Covid-19 - Firdo Andiri Suryo; Dhedhy Yuliawan; Mohkamad Firdaus (Jurnal Literasi Olahraga, 2021)
The Covid-19 pandemic has led to the implementation of online learning, so students are only at home when carrying out theoretical and practical lectures. This is the basis for this research to be carried out. The formulation of the problem in this study is how the physical activity of the students of the UN PGRI Kediri Physical Education Study Program during the Covid-19 Pandemic?. This study uses survey research techniques with quantitative methods. So that the data collection uses a Global Physical Activity Questionnaire (GPA-Q) questionnaire with instrument validity and reliability of 0.48 and 0.67-0.73. Then the instrument was compiled using a google form because the research was carried out during the Covid-19 pandemic. The research subjects were 448 students with the sampling technique using a sample quota. The results of the study showed that the physical activity of the students of the National Physical Education Study Program PGRI Kediri had a high intensity with the following criteria, the physical activity of students in the High category was 370 students or 82.59%, the physical activity of students in the Medium category was 78 students or 17.41%, the physical activity of students in the Low category there are 0 students or 0%. The highest frequency is in the high category with 370 students or 82.59%, so it can be concluded that the physical activity of the UN PGRI Kediri Physical Education Study Program students during the Covid-19 Pandemic is in the High category